Perbandingan Efek Afrodisiaka Infusa dan Ekstrak n-Heksana Kuncup Bunga Cengkeh (Syzygium aromaticum L.) pada Tikus Putih Jantan Galur Wistar - ARIKA WIDYARINI; YUL MARIYAH; WIWIN HERDWIANI (Jurnal Farmasi Indonesia, 2012)
Clove (Syzygium aromaticum L.) flower bud is one of medicinal plant that is used as aphrodisiac. The study was aimed to find out the aphrodisiac effect of infuse and n-hexane extract of clove flower buds on climbing frequency of white male rats wistar strain and to know a higher aphrodisiac effect between infuse and n-hexane extract of clove flower buds. The test animals used were divided into four test groups. Group I (negative control) was given CMC 1%. Group II (positive control) was given Dji Wo capsul dose of 9 mg/200 g BW. Group III was given the n-hexane extract dose of 350 mg/200 g BW. Group IV was given the infuse dose of 350 mg/200 g BW. All preparations were given orally twice a day (morning and evening) for 5 days. At day-5, climbing frequency was observed and making vaginal smear to observe the male rat sperms. The climbing frequency data was analyzed using two ways Anova followed by Dunnett T3 test at 95% confidence. The result showed that infuse and n-hexane extract of clove flower buds had aphrodisiac effect on white male rat wistar strain and the infuse of clove flower buds had aphrodisiac effect similar with n-hexane extract.